2019
DOI: 10.9758/cpn.2019.17.3.423
|View full text |Cite
|
Sign up to set email alerts
|

Switching Antipsychotics to Blonanserin in Patients with Schizophrenia: An Open-label, Prospective, Multicenter Study

Abstract: Objective This study was performed to investigate the efficacy and tolerability of blonanserin in schizophrenic patients who were previously treated with other antipsychotics but, due to insufficient response, were switched to blonanserin. Methods A total of 52 patients with schizophrenia who were unresponsive to treatment with antipsychotic monotherapy or combination therapy were recruited into this 12-week, open-label, prospective, multicenter study. Patients were swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…From February 2012 to February 2013, the results of a randomized, double-blind, double-dummy, parallelcontrolled multi-center phase III clinical trial with risperidone as the control drug showed that the efficacy of BNS for schizophrenia is comparable to that of risperidone (7). In the safety test of the drug, clinical trials conducted in China were consistent with clinical trials in Europe and America (5), Japan (5,8), and South Korea (6,9). No new ADRs or trends were reported.…”
Section: Introductionmentioning
confidence: 71%
“…From February 2012 to February 2013, the results of a randomized, double-blind, double-dummy, parallelcontrolled multi-center phase III clinical trial with risperidone as the control drug showed that the efficacy of BNS for schizophrenia is comparable to that of risperidone (7). In the safety test of the drug, clinical trials conducted in China were consistent with clinical trials in Europe and America (5), Japan (5,8), and South Korea (6,9). No new ADRs or trends were reported.…”
Section: Introductionmentioning
confidence: 71%